2007
DOI: 10.1063/1.2733752
|View full text |Cite
|
Sign up to set email alerts
|

Properties of light-emitting porous silicon photoetched in aqueous HF∕FeCl3 solution

Abstract: The formation of yellow-light-emitting porous silicon ͑PSi͒ layers in a HF solution with adding an oxidizing agent FeCl 3 is presented. The PSi layers are formed by photoetching under Xe lamp illumination. The photoluminescence ͑PL͒ intensity is strongly dependent on the FeCl 3 concentration and shows a maximum at x ϳ 25 wt % ͓50 wt % HF: ͑x wt % FeCl 3 in H 2 O͒ =1:1͔. The surface topography as characterized by atomic force microscopy reveals features on the order of 20Ϫ100 nm with a root-mean-squares roughne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 33 publications
(39 reference statements)
1
19
0
Order By: Relevance
“…2c). It is to be noted that the larger the E o value is in the positive (negative) scale, the stronger is the oxidation (reduction) agent (Adachi and Kubota 2007;Xu and Adachi 2007;Tomioka et al 2007). The absorption of photons results in the generation of electron-hole pairs.…”
Section: Photoetching Setupmentioning
confidence: 96%
See 1 more Smart Citation
“…2c). It is to be noted that the larger the E o value is in the positive (negative) scale, the stronger is the oxidation (reduction) agent (Adachi and Kubota 2007;Xu and Adachi 2007;Tomioka et al 2007). The absorption of photons results in the generation of electron-hole pairs.…”
Section: Photoetching Setupmentioning
confidence: 96%
“…In (Xu and Adachi 2007), the atomic force microscopy images were reported to show many irregularly shaped hillocks and voids distributed randomly over the entire PS surface. The observed root-mean-squares roughnesses were a few nanometers.…”
Section: Ps Layers Formed By Photoetchingmentioning
confidence: 98%
“…The etch rate is also directly proportional to the concentration of either Fe 3+ or VO 2 + ; however, unlike HNO 3 , there is no threshold concentration below which stain etching does not occur. The formation of por-Si films in Fe 3+ + HF solutions under illumination with a Xe lamp has also been studied (Xu and Adachi 2007). Kolasinski and Barclay (2013a) have demonstrated that the stoichiometry of stain etching is distinct from that of anodic por-Si formation.…”
Section: +mentioning
confidence: 98%
“…Some authors also demonstrated the formation of a luminescent PSi by photoetching in HF-based solutions under HeϪNe laser illumination. [5][6][7][8][9] More recently, we reported the formation of luminescent PSi layers by photoetching in a HF solution containing some oxidizing agents, such as KIO 3 , 10 I 2 , 11 and FeCl 3 , 12 and using an incoherent light source ͑Xe lamp͒. This method enabled to obtain a large ͑Ն20ϫ 20 mm 2 ͒, homogeneous PSi layer in a very short time ͑Ͻ10 min͒.…”
Section: Introductionmentioning
confidence: 99%
“…This method enabled to obtain a large ͑Ն20ϫ 20 mm 2 ͒, homogeneous PSi layer in a very short time ͑Ͻ10 min͒. [10][11][12] The stain and photoetched PSi films have been suggested as being similar in nature to the anodically etched PSi films. [4][5][6][7][8][9][10][11][12] The purpose of this article is to make clear the optical properties of PSi photoetched in aqueous HF/ I 2 solution.…”
Section: Introductionmentioning
confidence: 99%